Eksistensi Wazan Dalam Pembentukan Kata Baru Dalam Bahasa Arab - Pakaya, Nurul Aini Pakaya; R. Saleh, Sriwahyuningsih; Doni, Chaterina Puteri (Language Development Center, 2023)
Background: In Arabic linguistics, morphology is a parameter (mizan) of Arabic that is needed in the syntactic subsystem, because words act as input units to form sentences and words are the basis of a language. Purpose: This research article discusses morphological changes that occur in the process of At-ta’rib (Arabization) in the form of absorption and formation of foreign words and terms into Arabic. Method: This research is literature research. Primary data sources are obtained from al-Jazirah magazine, and secondary data sources are literature, both in the form of books, journals, and research results. Data collection is done with documentation, listening, and note-taking techniques. Data analysis techniques using; 1) open coding, 2) grounded theory analysis are described descriptively. Results and Discussion: The results of this study explain that in the structure of the word At-ta’rib (Arabization), in addition to using and utilizing existing rules with qiyas and wazan-wazan (word scales) in Arabic, modern morphology that comes with the process of affixation also plays an important role in the formation of new words and changing the class of words from certain lexical elements to other lexical elements. Based on the results of the study, the structure of the word At-ta’rib (Arabization) uses several forms of affixation, namely the form of perfixes الاستراتجي)), Infix ماجستير)), suffix تكنولوجيا)), and circulate الديموقراطي)). Conclusions and Implications: Modern morphological changes can be used as a basis that Arabic vocabulary always adapts to the needs and developments of the times. The formation of new vocabulary as a result of modern arabization (At-ta'rib) involves the morphological processes of